PENGARUH KOMPOSISI DAN PENDIDIKAN DEWAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DALAM PELAKSANAAN GOOD CORPORATE GOVERNANCE PADA BADAN USAHA MILIK NEGARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - SRI RAHAYU; SAMIAJI NUGROHO (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
This research is aims to analyze the influence of board composition and board education in implementation of good corporate governance to corporate value. Research carried out to the amount of State Owned Enterprisesin the period of 2010until 2012. Analyze the influence board of the company examine namely: number of commissioners, the number of independent commissioners, the number of directors, the business educational background of commissioner and business education background of directors on corporate value, where the value ofthe company using the value of Tobin's qandÂ  the value ofReturn on Assets(ROA).The results showed that all the variables are jointly significantly affect the value of Tobin'sq and ROA. But partially variable that affect the value of Tobin's q is only the educational background of directors with the direction of a positive relationship. While partially variable that affect the value of ROA is only the number of directors to the negative direction of the relationship.